Microbiology of mole crickets (Gryllotalpa orientalis) sold in representative sources from Luzon, Philippines - Astillero, Silke Sabodogo (2007)
ABSTRACT The consumption of Philippine mole crickets or kamaru is gaining popularity thus the need to establish quality and safety. This study evaluated the microbial quality of Philippine mole crickets or kamaru. Documentations of harvesting, processing and vending of kamaru were done and related to the microbial counts obtained. The microbial quality parameters included total plate count (TPC), total staphylococcal count (TSC), total coliform count (TCC), generic E. coli count (GEC), and detection of Salmonella spp. The results showed TPC of live, pre-processed, and ready-to-eat kamaru ranging from 7.54 to 9.01, <4.40 to 6.39, and <2.48 to <4.40 log10 cfu/g respectively. The TSC of live, pre-processed, and ready-to-eat ranged from 6.28 to 8.18, <2.30 to 5.46, <2.00 to <3.74 log10 cfu/g respectively. It was also found that TCC and GEC ranged from <6.00 to <8.00 log10 cfu/g and <5.00 to <8.00 for live samples, <1.00 to <3.18 log10 cfu/g and <1.00 to <3.00 for pre-processed, and <1.00 to <1.59 log10 cfu/g in both parameters for ready-to-eat. The presence of Salmonella spp. was also observed in the various market forms. It was found that pre-processing and further cooking were able to control the microorganisms with respect to quality thus extending the shelf-life of the product.